2022
DOI: 10.1002/ehf2.14178
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and structural remodelling after ablation of atrial fibrillation in heart failure with mildly reduced or mid‐range ejection fraction

Abstract: AimsThe efficacy of catheter ablation (CA) on clinical outcomes and cardiac structural remodelling in atrial fibrillation (AF) patients with HF with mildly reduced or mid-range ejection fraction (HFmrEF) remains unclear. We aimed to compare the efficacy of CA with medical therapy (MT) in AF patients with HFmrEF. Methods and resultsWe retrospectively screened a total of 36 879 patients with AF between 2005 and 2020. Patients who were initially diagnosed with echocardiography-proved HFmrEF and had follow-up echo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In patients undergoing CA, a reduction in the left atria (LA) diameter and a subsequent improvement in LVEF were observed in the study by Lee et al [ 22 ]. The mechanism of LA dysfunction changes based on the degree of HF.…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…In patients undergoing CA, a reduction in the left atria (LA) diameter and a subsequent improvement in LVEF were observed in the study by Lee et al [ 22 ]. The mechanism of LA dysfunction changes based on the degree of HF.…”
Section: Reviewmentioning
confidence: 99%
“…In another trial, it was observed that SR maintenance was essential for preventing mortality [ 16 , 50 ]. The superiority of CA versus AADs has been demonstrated in the randomized AATAC trial, in which HFrEF patients with persistent AF receiving CA were significantly more likely to be free from AF recurrence (70% vs. 34%, P < 0.001) and have lower mortality rate (8% vs. 18%) than the patient receiving amiodarone [ 22 , 49 , 51 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations